2008
DOI: 10.1007/s10549-008-9927-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression meta-analysis identifies chromosomal regions and candidate genes involved in breast cancer metastasis

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. Abstract Breast cancer cells exhibit complex karyotypic alterations causing deregulation of numerous genes. Some of these genes are probably causal for cancer formation and local growth whereas others are causal for the various steps of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 43 publications
3
56
0
Order By: Relevance
“…Consistent with previous reports, 3,16 extensive DNA gains occurred at the Yiya locus in all the cancer samples. The highest levels of genomic DNA amplification were found in rectal and gastric cancer (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous reports, 3,16 extensive DNA gains occurred at the Yiya locus in all the cancer samples. The highest levels of genomic DNA amplification were found in rectal and gastric cancer (Fig.…”
Section: Resultssupporting
confidence: 92%
“…3 Supporting the data, a more recent genome-wide association study also found 1q41 as a susceptibility locus in colorectal cancers, suggesting its potential role in carcinogenesis. 2 Even with this and other convincing association evidence, no cancer-causing genes have been characterized in this region, which suggests that other genetic elements may be involved in this process.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations